2017
DOI: 10.3390/nu9030278
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Liquid Fructose to a Western-Type Diet in LDL-R−/− Mice Induces Liver Inflammation and Fibrogenesis Markers without Disrupting Insulin Receptor Signalling after an Insulin Challenge

Abstract: A high consumption of fat and simple sugars, especially fructose, has been related to the development of insulin resistance, but the mechanisms involved in the effects of these nutrients are not fully understood. This study investigates the effects of a Western-type diet and liquid fructose supplementation, alone and combined, on insulin signalling and inflammation in low-density lipoprotein (LDL) receptor-deficient mice (LDL-R−/−). LDL-R−/− mice were fed chow or Western diet ±15% fructose solution for 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(73 reference statements)
0
7
1
Order By: Relevance
“…In contrast, Cigliano et al recently reported hippocampal inflammation in young and adult male rats after short-term consumption of fructose in solid form [44], and suggested that inflammation may be linked to increased intestinal permeability and microbiota remodeling [44,50]. The difference between our results and those from Cigliano et al may lie in the way the body handles solid compared to liquid fructose; thus, we have previously shown that feeding mice with a Western-type solid diet as a source of fructose increases intestinal permeability to bacterial toxins, whereas liquid fructose supplementation (15% w/v) does not [51].…”
Section: Discussioncontrasting
confidence: 80%
“…In contrast, Cigliano et al recently reported hippocampal inflammation in young and adult male rats after short-term consumption of fructose in solid form [44], and suggested that inflammation may be linked to increased intestinal permeability and microbiota remodeling [44,50]. The difference between our results and those from Cigliano et al may lie in the way the body handles solid compared to liquid fructose; thus, we have previously shown that feeding mice with a Western-type solid diet as a source of fructose increases intestinal permeability to bacterial toxins, whereas liquid fructose supplementation (15% w/v) does not [51].…”
Section: Discussioncontrasting
confidence: 80%
“…Fructose diet increased hepatic levels of proinflammatory cytokines TNFα and IL-1β, while pro-inflammatory IL-6 and anti-inflammatory cytokines IL-4 and IL-10 remained unchanged, consistent with hepatic inflammation [49,50]. The increased hepatic cytokine levels could be mediated by proinflammatory NFκB and JNK signaling pathways in the liver [51].…”
Section: Discussionmentioning
confidence: 65%
“…Supplementation of liquid fructose to western‐diet fed Ldlr −/− mice demonstrated similar results with the mice developing increased atheromatous plaque driven by increased monocyte/macrophage infiltration and local inflammation. Importantly, atherosclerotic plaque size strongly correlated with plasma lipid levels (Sangüesa et al, 2017). Another method that has been described to model the metabolic syndrome associated with diabetes is the incorporation of low‐dose streptozotocin along with high fat feeding.…”
Section: Animal Models Of Diabetes‐associated Macrovascular Diseasesmentioning
confidence: 99%